Clinical Pharmacokinetics and Safety of Orally Administered VH4011499, a New HIV-1 Capsid Inhibitor, in Adults Without HIV - Nilay Thakkar; Rulan Griesel; Amy Pierce; Veronica Bainbridge; Bronagh Shepherd; Konstantinos Angelis; Andrew Tomlinson; Yash Gandhi; Darin Brimhall; Brian Spears; Daijha Anderson; Emma Pinnick; et al. (Infectious Diseases and Therapy)
Abstract Introduction This first-time-in-human study describes the pharmacokinetics, drug–drug interaction potential, and safety of VH4011499 (VH-499), a new HIV-1 capsid inhibitor. Methods This double-blind, randomized, placebo-controlled, phase 1 study evaluated VH-499 in adults without HIV administered orally as single ascending doses as powder-in-bottle (PiB; part 1) and tablet (part 3) formulations and as multiple ascending doses as PiB formulation dosed once daily for 14 days (part 2). Midazolam was used to evaluate the effect of VH-499 on cytochrome P450 3A (CYP3A) activity (part 2). Results Overall, 73 participants were included (VH-499, n = 56; placebo, n = 17). VH-499 plasma exposures were less than dose-proportional, with median time to maximum observed concentration of 8.0–12.0 h for the PiB formulation and 24.0 h for the tablet formulation. Geometric mean terminal half-life was 51.2–66.5 h (2–3 days). The tablet formulation resulted in 45–63% lower exposures compared with PiB. Concomitant midazolam administration after single and multiple VH-499 doses did not lead to clinically significant changes in midazolam or 1-hydroxymidazolam exposures; therefore, VH-499 is not expected to inhibit or induce CYP3A4. VH-499 was well tolerated. Adverse event (AE) frequency was comparable between placebo and VH-499 groups. VH-499-related AEs were predominantly grade 1. No serious AEs across VH-499 groups, AEs leading to withdrawal from drug/study, or deaths occurred. There were no trends in vital signs, electrocardiograms, or laboratory hematology parameters and no clinically relevant changes in chemistry parameters. Conclusion First-time-in-human data further characterize the pharmacokinetics of orally administered VH-499 and provide support for development of VH-499 as part of a complete long-acting regimen for HIV-1 treatment and prevention. Clinical Trial Registration ClinicalTrials.gov, NCT05393271.